(untitled) (Research, Society and Development, 2020)
Cutaneous wound can be defined as the loss of continuity of the integument and due to its high incidence of chronicity, it generates a significant clinical and socioeconomic impact on the health system. The Epidermal Growth Factor (EGF) and light emitting diode (LED) photobiomodulation therapy (PBMT) have been shown to be promising therapeutic strategies with good results for skin repair. Thus, the aim of this study is to provide, through a narrative review, an understanding of the current evidence available on the importance of EGF and PBMT to LED in tissue repair of skin wounds. The searches were performed in the bibliographic databases of PubMed / MEDLINE, Virtual Health Library (VHL), Web of Science and SciELO. The evidence found in this study reports that both EGF and PBMT to LED are effective in reducing the inflammatory process, increasing the number of fibroblasts, collagen deposition, formation of new blood vessels and in the dermis-like tissue area, as well as stimulating re-epithelialization of the wound. Thus, we can conclude that EGF and PBMT to LED are effective in modulating the inflammatory process and stimulating factors that optimize wound repair, and can be promising resources in the clinical treatment of skin wounds.